Impact of Socio-Economic Factors on Nutrition Efficiency: An Application of Data Envelopment Analysis - Pakravan-Charvadeh, Mohammad Reza; Flora, Cornelia Butler; Emrouznejad, Ali (Frontiers in Nutrition, 2022)
Abstract Background Paying particular attention to sustainable food consumption in low-income households is essential ‎‎for increasing human health. Due to the growing population globally, this concept will likely ‎become more ‎serious soon. ‎ Methods Following the importance of optimizing food consumption for ‎sustainability, in this study, a novel ‎methodology is introduced for calculating nutrient intake ‎efficiency and determining choices of ‎food to in ‎different locations. The impact of socio-economic factors on nutrition efficiency is ‎assessed. ‎Data Envelopment Analysis (DEA) and a Tobit model are used to achieve the goals. ‎Household ‎Consumption and Expenditure Surveys (HCES) of 30,000 rural and urban Iranian ‎households in all provinces in 2016 is analyzed. A Nutrient Efficiency Map (NEM) of Iran was ‎depicted by GIS ‎software. ‎ Results The results showed that many townships had nutrient efficiency scores of less than 70%. ‎Northeast ‎townships had the lowest scores, with an efficiency score of less than 50%. ‎Overall, townships ‎have lower efficiency in the North (seaside cities), East (desert cities), and North ‎East (isolated ‎cities) compared with other areas.‎ Conclusions ‎ Therefore, it is suggestible that the government ‎should modify the support policies and the ‎protection packages based on social, geographical‎‏,‏‎ and cultural status.‎